Design, Development and Testing of a Community Size Solar Cooker - Rathore, N S; Kothari, S (Journal of Agricultural Engineering, 2003)
A community size solar cooker capable of cooking 8 kg. of food per day for meeting the requirement of about 35-40 people has been designed and developed. The pay back period of cooker varies between 0.75 to 2.60 years depending upon fuel it replaces.